2018
DOI: 10.1021/acs.jafc.8b03416
|View full text |Cite
|
Sign up to set email alerts
|

Tracking, Behavior and Fate of 58 Pesticides Originated from Hops during Beer Brewing

Abstract: The study presents tracking of 58 pesticide residues associated with hops to estimate their carryover into brewed beer. The pesticides were spiked onto organic hops at a concentration of 15 mg/kg, and the wort was boiled with the artificially contaminated hops and fermented on a laboratory scale. Samples were collected during the whole brewing process and pesticide residues were extracted using a method known as QuEChERS (quick, easy, cheap, effective, rugged, and safe). An HPLC-HR-MS/MS method was developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…They used LLE and subsequent solid-liquid extraction (SLE), prior to quantification by HPLC/MS/MS. Dušek et al [124] carried out the evaluation of the persistence of 58 pesticides in beer, which were extracted using the Quick, Easy, Cheap, Effective, Rugged, and Safe method called QuEChERS for subsequent identification and quantification by HPLC/MS/MS. They determined that thermostable pesticides were the most potential risk category due to their persistence in the final product and consequent human exposure.…”
Section: Pesticidesmentioning
confidence: 99%
“…They used LLE and subsequent solid-liquid extraction (SLE), prior to quantification by HPLC/MS/MS. Dušek et al [124] carried out the evaluation of the persistence of 58 pesticides in beer, which were extracted using the Quick, Easy, Cheap, Effective, Rugged, and Safe method called QuEChERS for subsequent identification and quantification by HPLC/MS/MS. They determined that thermostable pesticides were the most potential risk category due to their persistence in the final product and consequent human exposure.…”
Section: Pesticidesmentioning
confidence: 99%
“…During the first step (malting), pesticide residues can remain on malt as pointed out by some authors. Subsequently, after the mashing and boiling steps, pesticides on the malt can pass into the wort in different amounts, depending on the process used, although it should be highlighted that the removal of trub and spent grains tends to decrease pesticide levels because most of them have low solubility in water. An excellent study can be found in the paper published by Inoue et al where the fate of 368 pesticide residues was investigated during beer brewing (Table ). Only a few pesticides remained at large ratios in beer.…”
Section: Use Of Pesticides On Barley and Hopmentioning
confidence: 99%
“…The correlation between the log K OW values and the residual ratios ( R W ) of 58 pesticides associated with hops to estimate their carryover into brewed beer was assessed by Dušek et al to forecast their behavior during wort boiling. R W was considered on the basis of pesticide amount in hopped wort related to the sum of amounts of the pesticide in spent hops and hopped wort.…”
Section: Evolution Of Pesticide Residues During Brewingmentioning
confidence: 99%
See 2 more Smart Citations